Climatic, topographic, and anthropogenic factors determine connectivity between current and future climate analogs in North America - Carroll, Carlos; Parks, Sean A.; Dobrowski, Solomon Z.; Roberts, David R. (Global change biology, 2018)
As climatic conditions shift in coming decades, persistence of many populations will depend on their ability to colonize habitat newly suitable for their climatic requirements. Opportunities for such range shifts may be limited unless areas that facilitate dispersal under climate change are identified and protected from land uses that impede movement. While many climate adaptation strategies focus on identifying refugia, this study is the first to characterize areas which merit protection for their role in promoting climate connectivity at a continental extent. We identified climate connectivity areas across North America by delineating paths between current climate types and their future analogs that avoided nonanalogous climates, and used centrality metrics to rank the contribution of each location to facilitating dispersal across the landscape. The distribution of connectivity areas was influenced by climatic and topographic factors at multiple spatial scales. Results were robust to uncertainty in the magnitude of future climate change arising from differing emissions scenarios and general circulation models, but sensitive to analysis extent and assumptions concerning dispersal behavior and maximum dispersal distance. Paths were funneled along north‐south trending passes and valley systems and away from areas of novel and disappearing climates. Climate connectivity areas, where many potential dispersal paths overlapped, were distinct from refugia and thus poorly captured by many existing conservation strategies. Existing protected areas with high connectivity values were found in southern Mexico, the southwestern US, and western and arctic Canada and Alaska. Ecoregions within the Isthmus of Tehuantepec, Great Plains, eastern temperate forests, high Arctic, and western Canadian Cordillera hold important climate connectivity areas which merit increased conservation focus due to anthropogenic pressures or current low levels of protection. Our coarse‐filter climate‐type‐based results complement and contextualize species‐specific analyses and add a missing dimension to climate adaptation planning by identifying landscape features which promote connectivity among refugia. The persistence of many species under climate change will depend on our ability to identify and protect areas that facilitate dispersal to newly climatically suitable habitat. We used centrality metrics to identify climate connectivity areas across North America by delineating paths between current climate types and their future analogs that avoided non‐analogous climates. Paths were funneled along north‐south trending passes and valley systems and away from areas of novel and disappearing climates. Climate connectivity areas, where many potential dispersal paths overlap, are distinct from refugia and thus poorly captured by many existing conservation strategies.